Pengaruh Jenis dan Lama Perendaman Krioprotektan Terhadap Viabilitas Benih Rosella (Hibiscus sabdariffa L.) Secara Kriopreservasi - Ahmad Afandy Harahap; Haryati Haryati; Luthfi A. M. Siregar (Universitas Sumatera Utara, 2015)
Cryopreservation is a technique for long-term storage nuftah plasma. In this technique cells and meristem or other parts of plants were frozen and stored in liquid nitrogen at a temperature -196°C. The objective of the reseacrh was to know effects of type and duration of soaking cryoprotectant on the viability of roselle seed in cryopreservation. This research was conducted at the Laboratory of Seed Technology Faculty of Agriculture, University of North Sumatra, Medan with a height ± 25 meters above sea level, from September to October 2014, using a randomized block design with 2 factors. The first factor is the type of cryoprotectant with 4 type of PVS1 ; PVS2; PVS3; PVS4 and the second factor of soaking cryoprotectant with 3 levels of 60 minutes; 90 minutes; 120 minutes. Parameter observed were the rate of germination (day), normal seedling (%), abnormal seedling (%), seeds die (%), vigor index, fresh weight of seedling (g), dry weight of seedling (g). The results showed soaking treatment of various types of cryoprotectant significant effect on the observation parameters the rate of germination (day), normal seedling (%), vigor index, fresh weight of seedling (g) and dry weight of seedling (g). Treatment of soaking cryoprotectant significant effect on the observation parameters abnormal seedling (%) and vigor index. Interaction type and duration of soaking cryoprotectant significant effect observation parameters on the rate of germination (day) and vigor index. Keywords: cryoprotectant, soaking time, cryopreservation, roselle seed